Spirochetes flagellar collar protein FlbB has astounding effects in orientation of periplasmic flagella, bacterial shape, motility, and assembly of motors in Borrelia burgdorferi. Issue 2 (9th August 2016) - Moon, Ki Hwan; Zhao, Xiaowei; Manne, Akarsh; Wang, Juyu; Yu, Zhou; Liu, Jun; Motaleb, Md A.
Summary: Borrelia burgdorferi, the causative agent of Lyme disease, is a highly motile spirochete, and motility, which is provided by its periplasmic flagella, is critical for every part of the spirochete's enzootic life cycle. Unlike externally flagellated bacteria, spirochetes possess a unique periplasmic flagellar structure called the collar. This spirochete‐specific novel component is linked to the flagellar basal body; however, nothing is known about the proteins encoding the collar or their function in any spirochete. To identify a collar protein and determine its function, we employed a comprehensive strategy that included genetic, biochemical, and microscopic analyses. We found that BB0286 (FlbB) is a novel flagellar motor protein, which is located around the flagellar basal body. Deletion of bb0286 has a profound effect on collar formation, assembly of other flagellar structures, morphology, and motility of the spirochete. Orientation of the flagella toward the cell body is critical for determination of wild‐type spirochete's wave‐like morphology and motility. Here, we provide the first evidence that FlbB is a key determinant of normal orientation of the flagella and collar assembly. Abstract : Spirochetes possess a unique periplasmic flagellar structure called collar that is absent from all externally flagellated bacteria studied to‐date. Here, we show for the first time that FlbB assembles around the flagellar basal body and plays important roles in collar assembly.